2019
DOI: 10.3390/cancers11091270
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Metastases of Unknown Primary: Biological Landscape and Clinical Overview

Abstract: Skeletal metastases of unknown primary (SMUP) represent a clinical challenge in dealing with patients diagnosed with bone metastases. Management of these patients has improved significantly in the past few years. however, it is fraught with a lack of evidence. While some patients have achieved impressive gains, a more systematic and tailored treatment is required. Nevertheless, in real-life practice, the outlook at the beginning of treatment for SMUP is decidedly somber. An incomplete translational relevance o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 126 publications
1
27
0
2
Order By: Relevance
“…However, in another study (GEFCAPI 04), where gene expression analysis was used to identify the most likely primary tumor, the best available targeted therapy and other treatments tailored to the primary tumor failed to improve disease progression or survival compared with chemotherapy [32]. For cancers of unknown primary origin taxanes are recognized as a chemotherapeutic option, so cabazitaxel could be a useful treatment option to be studied in these patients that have resistance to docetaxel [33,34]. Furthermore, it has been shown that patients with some specific subtypes of prostate cancer, such as luminal B (classified using gene expression signatures) experience significant improvements in time to castration resistance and overall survival following treatment with docetaxel plus androgen deprivation therapy (ADT) [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study (GEFCAPI 04), where gene expression analysis was used to identify the most likely primary tumor, the best available targeted therapy and other treatments tailored to the primary tumor failed to improve disease progression or survival compared with chemotherapy [32]. For cancers of unknown primary origin taxanes are recognized as a chemotherapeutic option, so cabazitaxel could be a useful treatment option to be studied in these patients that have resistance to docetaxel [33,34]. Furthermore, it has been shown that patients with some specific subtypes of prostate cancer, such as luminal B (classified using gene expression signatures) experience significant improvements in time to castration resistance and overall survival following treatment with docetaxel plus androgen deprivation therapy (ADT) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Taking this into consideration, applying CAP to canine osteosarcoma as an adjuvant therapy would increase the efficacy of chemotherapy. For example, bisphosphonate is a bone-modifying agent which is used in treating human bone cancer, as it reduces skeletal complications by inhibiting bone resorption [ 38 ]. Thus, it would be worth trying the application of CAP with bisphosphonate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating genetic and molecular features in a multistage diagnostic workup is essential for characterizing the biological SMUP profile to direct therapeutic decisions. SMUP is a comprehensive diagnosis and treatment plan that must be adapted to different pathophysiological complexities [ 16 ].…”
Section: Discussionmentioning
confidence: 99%